Diseño De Un Sistema De Indicadores Tecnológicos Para Identificar La Sostenibilidad Integral De La Ciudad De Riobamba, Ecuador - Francisco Silva; Catalina Verdugo; Paul Jínez; Sofía Basantes; Carlos Jara (European Scientific Journal, ESJ, 2018)
This paper focuses on designing a system of technological indicators that helps to determine the urban sustainability of the city of Riobamba. This was performed with the application of a matrix where a total of 68 indicators were identified at a city-wide level. After then, they were discriminated and classified into a total of 18 indicators. These indicators were classified according to temporality and applicability based on the collection of information. It was carried out through a review of bibliographic sources provided by the Municipal Autonomous Decentralized Government of Riobamba and with the preparation of a survey of 473 people who represent the sample. To determine its sustainability, the results obtained were applied in an SPSS database to be later evaluated in the Statistical Model. This model shows that the city has a 66% level of sustainability that is interpreted as medium sustainability. At the end, it was stated that Riobamba has 18 basic indicators as a starting point for the urban technological development that it is intended to achieve as a sustainable city.